Palladium-catalysed Csp3–H functionalisation of unactivated 8-aminoquinoline amides in deep eutectic solvents. Issue 35 (24th August 2022) - Marset, Xavier
Abstract : Enhanced reactivity of aliphatic amides via C–H activation has been found in deep eutectic solvents. The sustainability of the process is improved over previous reports and post-synthetic modifications are performed in these neoteric solvents. Abstract : The Csp 3 –H activation of aliphatic amides is described for the first time in deep eutectic solvents (DESs) without the need for Ag salts. The use of eutectic mixtures improves the yields obtained with volatile organic solvents, and allows for the reuse of the catalyst. Post-synthetic modifications can also be performed in DESs, increasing the sustainability of the process and the value of the products obtained.